The Effect of Optimism, Self-Efficacy, and Women's Leadership Style on Employee Performance in Pasuruan District Government with Assertive Communication as an Intervening Variable - Lilik Faiqotul Himmah; Ida Aju Brahmasari; Ida Aju Brahma Ratih (Indonesian Interdisciplinary Journal of Sharia Economics)
The purpose of this study was to prove and analyze the influence of optimism, self-efficacy, and women's leadership style on employee performance in the Pasuruan Regency Government with assertive communication as an intervening variable. The type of research used is quantitative, with a population of 2001 respondents from 7 Pasuruan Regency Government Offices and a sample of 333 respondents. Data collection was carried out using a questionnaire via Google Form and measured using a Likert scale. The analysis technique used the Structural Equation Model (SEM) tool, and then the Partial Least Square (PLS) program was used. The results of this study indicate that: 1) Optimism has a significant positive effect on assertive communication in the Pasuruan Regency Government. 2) Optimism has a significant effect on the performance of Pasuruan Regency Government employees. 3) Self-efficacy has a significant positive effect on assertive communication in the Pasuruan Regency Government. 4) Self-efficacy has a significant positive effect on the performance of Pasuruan Regency Government employees. 5) Women's leadership style has a significant positive effect on assertive communication in the Pasuruan Regency Government. 6) Women's leadership style has a significant positive effect on the performance of Pasuruan Regency Government employees. 7) Assertive communication has a significant positive effect on the performance of Pasuruan Regency Government employees. The recommendation from this study is that the Pasuruan Regency Government is expected to optimize women's leadership style by encouraging training that focuses on assertive communication so that it can create a collaborative and productive work environment. This step can contribute significantly to improving employee performance and supporting the achievement of organizational goals.